SINTESIS PLASTIK BIODEGRADABLE BERBAHAN KOMPOSIT PATI SAGU-KITOSAN SISIK IKAN KATAMBA (Lethrinus lentjam) - Anwar Said (Universitas Lambung Mangkurat, 2018)
Abstract. Biodegradable plastic is a low molecular weight polymer material that almost all of its constituent components come from renewable materials. One of the natural materials that can be used as biodegradable plastic raw materials is starch derived from sago. Sago is one of the plants that has starch about 75.88% so it has a potential to be used as raw material in the manufacture of biodegradable plastics. To improve the structure of biodegradable plastic, chitosan was used which was derived from the scales of Katamba fish. Synthesis of biodegradable plastic from sago extract by adding chitosan derived from Katamba fish scales which then analyzed its morphology characteristics by SEM (Scanning Electron Microscope). This research used pure experimental research design in laboratory (true experimental research), the research was the making of starch-chitosan composite as the main material in the production of plastic which was then done morphological analysis. The results of this study revealed the biodegradable plastic with the appearance of clear white transparent, smooth surface, and medium elasticity with the morphological characteristics through SEM observations with 5μm-20 μm magnification seen a solid plastic surface with a flat texture. Keywords: biodegredable plastics, extract of Sago, Katamba chitosan